Unexpected inverse correlation between Native American ancestry and Asian American variants of HPV16 in admixed Colombian cervical cancer cases (2014)
European (E) variants of HPV 16 are evenly distributed among world regions, meanwhile,Non-European variants such as European-Asian (EAs), Asian American (AA) and African (Af) are mostly confined to Eastern Asia.